2020
DOI: 10.3389/fpls.2020.00228
|View full text |Cite
|
Sign up to set email alerts
|

Control Effects of Chelonus munakatae Against Chilo suppressalis and Impact on Greenhouse Gas Emissions From Paddy Fields

Abstract: Field and pot experiments were conducted to investigate the control effects of parasitoid wasps (Chelonus munakatae Munakata) on striped rice stem borers and their impacts on N 2 O and CH 4 emissions from paddy fields. Three treatments including no insect (NI), striped stem borer (CS) and parasitoid wasp + striped stem borer (CS+CM) were implemented. The abundance of GHG-related microorganisms in soils was determined by absolute real-time qPCR. Compared with NI, CS and CS+CM significantly increased the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Kanter and Searchinger [89] analyzed metadata and reported that enhanced-efficiency fertilizers, using nitrification inhibitors and polymer coatings, could reduce N2O emissions and nitrogen leaching by approximately 25-60%. Meanwhile, Fan et al [90], suggested that reducing pesticide application by adopting the use of biological control could reduce GHG emissions.…”
Section: Greenhouse Gas Emissions and Carbon Footprint Of Of And Cvfmentioning
confidence: 99%
“…Kanter and Searchinger [89] analyzed metadata and reported that enhanced-efficiency fertilizers, using nitrification inhibitors and polymer coatings, could reduce N2O emissions and nitrogen leaching by approximately 25-60%. Meanwhile, Fan et al [90], suggested that reducing pesticide application by adopting the use of biological control could reduce GHG emissions.…”
Section: Greenhouse Gas Emissions and Carbon Footprint Of Of And Cvfmentioning
confidence: 99%
“…However, chemical herbicides also harm other crops and contaminate the soil. In addition, the other negative impact of using herbicides is greenhouse gas (GHG) emissions 8 10 . Biological control is supposed to be long-lasting, with no adverse effect on nontarget species, and an eco-friendlier solution to control invasive species.…”
Section: Introductionmentioning
confidence: 99%